Adaptive Models of Child-Friendly School Management: Integrating Policy, Teacher Competence, and Leadership Communication - Puspa Herliana; Ahmad Suriansyah; Sulistiyana Sulistiyana; Aslamiah Aslamiah (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examines management strategies for child-friendly school environments, focusing on policy, teacher competence, and principal communication in fostering inclusive culture. Using a qualitative multi-site design, the research was conducted in two secondary schools in Kotabaru District, South Kalimantan. Data were collected through interviews, participatory observation, and documentation, then analyzed inductively using the Miles and Huberman model, supported by NVivo 14. Data trustworthiness was ensured through triangulation of sources, methods, and theories, as well as systematic documentation. Findings show that SMP Negeri 1 applied structured, policy-based strategies, including anti-bullying regulations, teacher training, and external collaboration, whereas SMP Negeri 7 emphasized religious character, environmental care, and creative adaptation to limited facilities. Teacher competence improved through project-based learning and inclusive pedagogy, while principals used transparent, participatory communication with teachers, parents, and communities. The study proposes an adaptive multidimensional framework integrating policy, culture, and leadership communication for sustainable child-friendly school governance and inclusive educational improvement across diverse institutional and social contexts in Indonesia.